Samos, Griechenland. Notizen zu Samos während der NS-Zeit - Kankeleit, Alexandra (e-Forschungsberichte des DAI, 2020)
In the 1930s, the excavation at the Heraion of Samos was seen as the German Archaeological Institute’s (DAI) “most exceptional undertaking”. Numerous publications document the important discoveries and valuable scientific knowledge gained on the island. The outbreak of World War Two and the subsequent occupation of Greece led to a cessation of all DAI activities on Samos for a period of several years. Samos was subject to three successive occupations during the war: first under Italy (May 1941 to September 1943), then Britain (“temporary liberation” from September to November 1943), and finally under the Germans (November 1943 to September 1944, the liberation took place on 5 October 1944). The island, situated in the Eastern Aegean Sea in direct proximity to neutral Turkey, was in a state of constant emergency. During the occupation, Samos endured looting, bombardments and massacres. Under these conditions of general lawlessness, archaeological artefacts were also at great risk – a topic that will be the focus of my article.